Biological and economic aspects of Melanagromyza socolena (Diptera: Agromyzidae) a new pest of the garden tomato - DE POLANÍA, INGEBORG ZENNER (Revista Colombiana de Entomología, 1995)
The finding of an insect, responsible for the drop of tomato flower buds, induced basic studies under field and laboratory conditions, where the development of the host and the insect life cycle were followed simultaneously. In order to determine the number of instars, weekly, 100 flower buds were analyzed. Percent parasitism was appraised during the reproductive cycle of tomato, collecting weekly, during one hour, affected buds. Economic aspects were estimated analyzing attack and losses caused by the pest on 33 plants. The insect detected belongs to the new specieMelanagromyza socolena Sanabria de Arévalo y Zenner de Polanía (Diptera: Agromyzidae), which passes its cycle within the flower bud. The adult, a black colored fly with a metallic dark green sheen, places one egg within the bud; the egg is white and lasts from 2 - 3 days. The larva, also white, go through three instars within 5 - 7 days, feeding on anthers, pistil and The pupa develops between the sepals at the base of the bud, having a mean duration of 11 days. In the moment of pupal formation, the flower bud separates at the abscision point. As parasites, the pteromalids Heteroschema rugosopunctata (Ashmead) and Syntomopus sp., and a genus near Zaeucoila (Eucoilidae) were detected and together cause up to 54.76% parasitism. The bud drop increases as the flowering period advance. In the inferior third of the tomato plant, an average of 4.03% of buds is lost, in the middle third 19,88% and in the superior third 28,60%, which corresponds to an average loss of 0.733 kg of possible fruits per plant. Per hectare, the losses may reach and exceed 15 tons. Up to now, the insect has been at altitudes between 1,400 and 1,800 masl in some tomato producing towns of Cundinamarca, but its presence is suspected in all the departments.